Rural Elderly Caregivers: Exploring Folk Home Remedy Use and Health Promotion Activities - Leisa R. Easom; Mary Ellen Quinn (Rural Nurse Organization; Binghamton University, 2006)
This exploratory study examined folk home remedy behavior and engagement in health promotion activities in rural elderly caregivers. Data was obtained with a self-report questionnaire, from a probability sample of 80 caregivers (age range = 65-84 years). Results indicated that caregivers were very involved in health promotion activities, except for exercise. Participants had high rates of folk home remedy use. Emotional health was a significant positive predictor of engagement in health promotion activities and an important factor for a healthy lifestyle in the rural, elderly caregiver. The high frequency of folk home remedy use indicates that nursing assessments should include questions about the use of folk home remedies as a measure of health promotion.